A novel ATP1A2 gene mutation in familial hemiplegic migraine and epilepsy. (January 2014) - Costa, Cinzia; Prontera, Paolo; Sarchielli, Paola; Tonelli, Alessandra; Bassi, Maria Teresa; Cupini, Letizia Maria; Caproni, Stefano; Siliquini, Sabrina; Donti, Emilio; Calabresi, Paolo
Background: Familial hemiplegic migraine (FHM) is a rare autosomal dominant migraine subtype, characterized by fully reversible motor weakness as a specific symptom of aura. Mutations in the ion transportation coding genes CACNA1A, ATP1A2 and SCN1A are responsible for the FHM phenotype. Moreover, some mutations in ATP1A2 or SCN1A also may lead to epilepsy. Case: Here we report on a three-generation family with five patients having a novel ATP1A2 mutation on exon 19, causing guanine-to-adenine substitution (c.2620G>A, p.Gly874Ser) that co-segregated in the five living relatives with migraine, four of whom had hemiplegic migraine. Moreover, three patients presented with epilepsy, one of whom had generalized epilepsy with febrile seizures plus (GEFS+). Conclusions: The present study provides further evidence on the involvement of ATP1A2 mutations in both migraine and epilepsy, underlying the relevance of genetic analysis in families with a comorbidity of both disorders.